Regulation of cell pH by ambient bicarbonate, carbon dioxide tension, and pH in the rabbit proximal convoluted tubule. - Krapf, R (1988)
To study the regulation of cell pH by ambient pH, carbon dioxide tension (PCO2), and bicarbonate (HCO3), cell pH was measured in the isolated, in vitro microperfused rabbit proximal convoluted tubule using the fluorescent dye (2',7')-bis-(carboxyethyl)-(5,6)-carboxyfluorescein. For the same changes in external pH, changes in [HCO3] and PCO2 affected cell pH similarly ([HCO3]: pHi/pHe = 0.67, PCO2: pHi/pHe = 0.64, NS). Isohydric changes in extracellular [HCO3] and PCO2 did not change cell pH significantly. Changes in peritubular [HCO3] elicited larger changes in cell pH than changes in luminal [HCO3], which were enhanced by peritubular 4-acetamido-4'-isothiocyanostilbene-2,2'-disulfonate (SITS). The cell pH defense against acute increases and decreases in PCO2 was inhibited by sodium, but not by chloride removal. Peritubular SITS inhibited the cell pH defense against increases and decreases of PCO2, whereas luminal amiloride inhibited cell pH defense against increases in PCO2. Conclusions: (a) Steady-state cell pH changes in response to changes in extracellular [HCO3] and PCO2 are quantitatively similar for a given change in extracellular pH; (b) the rate of the basolateral Na/(HCO3)3 cotransporter is a more important determinant of cell pH than the rate of the apical membrane mechanism(s); (c) cell pH defense against acute changes in PCO2 depends on the basolateral Na/(HCO3)3 cotransporter (acid and alkaline loads) and the luminal Na/H antiporter (acid loads).